ChestBioX-Gen: contextual biomedical report generation from chest X-ray images using BioGPT and co-attention mechanism - Ouis, Mohammed Yasser; Akhloufi, Moulay A. (Frontiers in Imaging, 2024)
Efficient and accurate radiology reporting is critical in modern healthcare for timely diagnosis and patient care. In this paper, we present a novel deep learning approach that leverages BioGPT and co-attention mechanisms for automatic chest X-ray report generation. Our model, termed "ChestBioX-Gen" is designed to bridge the gap between medical images and textual reports. BioGPT, a biological language model, contributes its contextual understanding to the task, while the co-attention mechanism efficiently aligns relevant regions of the image with textual descriptions. This collaborative combination enables ChestBioX-Gen to generate coherent and contextually accurate reports that embed complex medical findings. Our model not only reduces the burden on radiologists but also enhances the consistency and quality of reports.By automating the report generation process, ChestBioX-Gen contributes to faster diagnoses and improved patient care. Quantitative evaluations, measured through BLEU-N and Rouge-L metrics, demonstrate the model's proficiency in producing clinically relevant reports with scores of 0.6685, 0.6247, 0.5689, 0.4806, and 0.7742 on BLUE 1, 2, 3, 4, and Rouge-L, respectively. In conclusion, the integration of BioGPT and co-attention mechanisms in ChestBioX-Gen represents an advancement in AI-driven medical image analysis. As radiology reporting plays a critical role in healthcare, our model holds the potential to revolutionize how medical insights are extracted and communicated, ultimately benefiting both radiologists and patients.